Atypical presentation of Prader-Willi syndrome with Klinefelter (XXY karytype) and craniosynostosis Síndrome de Prader-Willi em paciente com Klinefelter (cariótipo XXY) e craniossinostose - Daniel R. Carvalho; Clovis S. Trad; João M. Pina-Neto (Arquivos de Neuro-Psiquiatria)
Prader-Willi syndrome is a mental retardation genetic disorder also characterized by hypogonadism, hyperphagia and obesity. We report on a four-years-old boy, born to consanguineous parents, with uncommon co-occurrence of Prader-Willi syndrome, 47,XXY karyotype (Klinefelter syndrome) and coronal craniosynostosis. These are different unrelated conditions and it was not described before in the same patient to the best of our knowledge. A síndrome de Prader-Willi é afecção genética de deficiência mental associada a hipogonadismo hipogonadotrófico, hiperfagia e obesidade. Descrevemos o caso de menino de 4 anos de idade, filho de casal consangüíneo, apresentando três condições clínicas não relacionadas: síndrome de Prader-Willi, cariótipo 47,XXY (compatível com síndrome de Klinefelter) e craniossinostose coronal. Ao nosso conhecimento, não foi relatado caso semelhante previamente na literatura.